Analisa Dampak Perusahaan dan Sertifikasi Lingkungan Terhadap Pengungkapan Corporate Social Responsibility (CSR) - Dini Apriyani; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
There are two reasons that can drive companies to participate in CSR. Certain companies believe that performing customer service (CSR) will allow the company to achieve better economic outcomes (Resource Based Theory), while other companies believe that doing so will give them a competitive advantage that sets them apart from their competitors. Stakeholders’ expectations, so CSR and their reports serve as legitimization to demonstrate their compliance with those expectations (Legitimacy Theory). Using legitimacy theory, this study aims to find empirical evidence on how international experience, consumer perspective, and the acquisition of environmental certifications impact the extent of CSR disclosure. A sample of 168 company-years was obtained using the target population of publicly listed manufacturing companies on the IDX that made CSR reports in 2011 and 2012.